Galen vein aneurysm malformation in pediatric patients: from diagnosis to treatment (Research, Society and Development, 2022)
Arteriovenous malformation of the vein of Galen named after Galen of Pergamum (gr. Γαληνός, also known as Aelius Galenus or Claudius Galenus) (129-199 AD), accounts for 1% of intracranial vascular malformations. It is characterized by marked dilatation of the vein of Galen, containing multiple arteriovenous fistulas that open into a middle vein of the forebrain called the vein of Markowski, precursor of the vein of Galen. During the perinatal period, the first clinical manifestation is usually heart failure, often in the first day or two of life, and may also present with hydrocephalus, unusually prominent veins on the face and scalp, developmental delays, persistent headache. and in very rare cases, a hemorrhage in the brain. The causes of Galen vein malformation occur during a baby's early prenatal development, usually during the first trimester, it is not known exactly what causes a MAVG but it is likely to be genetic, MAVG sometimes but not always occurs with vascular anomalies that affect other parts of the body. The diagnosis can be obtained from pregnancy through gestational ultrasound and, later, through transfontanellar ultrasound, magnetic resonance imaging and angiography, which is the standard exam. The best treatment for MAVG is endovascular embolization by the transarterial or transvenous technique, open surgery is reserved for cases of failure of endovascular embolization or associated with it when necessary. Its prognosis is linked to the initial clinic, early diagnosis and surgical correction at the right time.